(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The adoption of the administrative act is carried out on the basis of clearly defined procedures in our legislation of the procedure. In particular, according to Article 53 of the law”on administrative procedures", an administrative act must be legal, justified, fair, clear and understandable. In the substantiating part of the administrative act, all the actual and legal basis of the adopted administrative act must be cited. Currently, we are witnessing that these requirements do not apply to administrative acts that are contrary to the interests of the person concerned, or impose a certain obligation or prevent the implementation of certain acts. In German administrative law, such acts are interpreted as administrative acts[1]. In this regard, we will consider the practice of accepting administrative acts in several developed countries. “Administrative proceedings in Japan took effect on November 12, 1993. It is legally regulated by the law” on administrative proceedings”.